THE DEVELOPMENT OF ‘DELIKAN’ LEARNING MODEL TO INCREASE THE RHYTHM NOTATION COMPREHENSION IN TEACHING MUSIC TOWARD THE TEACHERS OF ART AND CULTURE MGMP OF JUNIOR HIGH SCHOOLS IN PADANG PARIAMAN REGENCY - Esy Maestro; Yos Sudarman (Fakultas Bahasa dan Seni UNP, 2014)
PENGEMBANGAN MODEL PEMBELAJARAN DELIKAN UNTUK MENINGKATKAN PEMAHAMAN NOTASI IRAMA PADA PELAJARAN SENI MUSIK BAGI GURU-GURU PESERTA MGMP SENI DAN BUDAYA TINGKAT SMP DI KABUPATEN PADANG PARIAMANAbstractThis research is about Delikan (Listen-See-Do) learning model, the model of learning that can be used in teaching rhythm and notation, where this model can be combined between listening method the design of sounds/voices, see the notation, rhythm, and do practicum read, write or practice the notation. The advantages this model is at the